The GmCYCLOPS paralogs regulate soybean nodulation and exhibit signatures during domestication - Yuanting Lei; Zhi Liu; Qiang Chen; Xintong Wu; Ming Li; Fulong Liu; Yuzhen Liu; Zhitong Yin; Siyuan Zhao; Pengshuo Shen; Yuan Zhao; Sobhi F. Lamlom; et al. (Plant Science, 2026)

Supranutritional dietary vitamin D3 promoted the skin wound healing in turbot, Scophthalmus maximus L. - Zhichu Chen; Yuanyuan Fang; Yuanting Li; Xinhua Chen; Mingzhu Pan; María Ángeles Esteban; Kangsen Mai; Yanjiao Zhang; Dong Huang (Aquaculture, 2026)

Study on the effect of air contamination in helium on the reliability of a Helium Joule-Thomson cryocooler - Pengcheng Qu; Zhichao Chen; Ziqi Wei; Yuanting Zhang; Jinjian Chu; Baoyu Yang; Xi Chen; Shaoshuai Liu (International Journal of Refrigeration, 2026)

High Carbohydrate Feeding Exacerbates Oxidative Stress and Intestinal Dysfunction in Red Seabream (Pagrus major) after Skin Wounding - Zhichu Chen; Yuanting Li; Yuanyuan Fang; Dong Huang; M. Ángeles Esteban; Yanjiao Zhang (Marine Biotechnology, 2026)

Polyphenol-mediated hierarchical porous hydrogel evaporators for accelerated water transport and reduced evaporation enthalpy - Xueqian Zhang; Hongtao Li; Bo Liang; Zikun Zou; Zhen Yang; Shaohui Xiong; Lei Yang; Xu Wang; Yang Chen; Yuanting Xu; Yiwen Li (Science Bulletin, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A vulnerability assessment with freight flow data of railway freight transportation network in Northeast China - Yuanting Jiang; Mei Han; Chao Chen; Yanhui Han; Fuhao Yu; Xiwei Mi (Journal of Transport Geography, 2025)

Diatom-inspired pH-responsive MOF coatings for active corrosion protection and sustained drag reduction in dynamic marine environments - Qidong Zha; Yuanting Deng; Zuozhu Yin; Yuhua Chen; Chan Xie; Zhen Hong; Yidan Luo; Mingshan Xue (Chemical Engineering Journal, 2025)

In vitro simulated digestion and fermentation characteristics of pumpkin polysaccharides and their effects on the human gut microbiota - Kejuan Li; Chun Wang; Jiajun Li; Hongyuan Cao; Qi Li; Lihong Ge; Yuanting Zhu; Yuzhi Miao; Chen Xia; Changbin Lin (Food Chemistry, 2025)

Mechanistic insights into ozone-induced asthma exacerbation: role of oxidative stress and IL-33 - Xinyi Fang; Bin Pan; Yuanting Xie; Wenpu Shao; Jingyu Li; Dongyang Han; Xiaoqing Hong; Wenyue Tu; Yifan Zhao; Jiaojiao Wu; Yaning Zhu; Yubin Zhang; et al. (Journal of Hazardous Materials, 2025)

Adsorption of radioiodine by metal sulfides and relevant derivatives - Wei Zheng; Xiaoxuan Chen; Hao Xu; Duxia Li; Yuanting Zhang; Wanliang Yang; Meisong Xu; Dehong Gong; Mengkui Tian (Journal of Cleaner Production, 2025)

Baseline Plasma GPX3 Level Predicts Efficacy of Insulin-Sensitization Drug Chiglitazar in Type 2 Diabetes - Zehui Cao; Haonan Chen; Qiaochu Chen; Chen Ding; Leming Shi; Yuanting Zheng (Phenomics, 2025)

Multi-omics Quality Assessment in Personalized Medicine Through European Infrastructure for Translational Medicine (EATRIS): An Overview - Patricia Alonso-Andrés; Davide Baldazzi; Qiaochu Chen; Elisa Conde Moreno; Lorena Crespo-Toro; Kati Donner; Petr Džubák; Sara Ekberg; Maria Laura García Bermejo; Daniela Gasparotto; Bishwa Ghimire; Jolein Gloerich; et al. (Phenomics, 2025)
Molecular characterization of a biological sample, e.g., with omics approaches, is fundamental for the development and implementation of personalized and precision medicine approaches. In this context, quality assessment is one of the most critical aspects. Accurate performance and interpretation of omics techniques is based on consensus, harmonization, and standardization of protocols, procedures, data analysis and reference values and materials. EATRIS, the European Infrastructure for Translational Medicine ( www.EATRIS.eu ), brings together resources and services to support researchers in developing their biomedical discoveries into novel translational tools and interventions for better health outcomes. Here we describe the efforts within the Horizon 2020 EATRIS-Plus project and activities of member facilities of EATRIS towards quality assessment of pre-clinical sample processing, clinical omics data generation, multi-omics data integration, and dissemination of the resources in a Multi-Omics Toolbox, which is the principal deliverable of the EATRIS-Plus project for the consolidation of EATRIS towards translational medicine.

Differences in spatial pattern of expressway passenger and freight flows based on OTC data: A case study of Guangdong, China - Yuanjun Li; Yuanting Li; Qitao Wu; Zhuo Chen; Yunhao Yang (Applied Geography, 2025)

Hydrology Modulates the Microplastics Composition and Transport Flux Across the River–Sea Interface in Zhanjiang Bay, China - Xiaoqing Chen; Peng Zhang; Jing Lu; Yuanting Chen; Jibiao Zhang (Journal of Marine Science and Engineering, 2025)
Estuaries act as significant pathways for plastic waste entry into the oceans, with microplastics (MPs) being intricately influenced by river and coastal hydrodynamics. MPs become entrapped within estuaries during transport, particularly at the river–sea interface, which impacted by tidal fluctuations. However, few studies have examined the role of the impacts of tidal variations on microplastic abundance and export flux at the river–sea interface across contrasting hydrological regimes (dry vs. wet seasons). In this study, we conducted observations to assess MPs abundance, composition, and flux in the Suixi Estuary of Zhanjiang Bay, China The results indicated an overall mean abundance of MPs of 91.1 ± 75.0 items/L, which was linked to tidal variations, decreasing during high tides and increasing during low tides. Transparent color, fibrous shape, and a size range of 100–330 μm were the most prevalent characteristics in water samples. MPs diversity was higher during the wet season compared to the dry season. In addition, the MPs influx was about 1.61 × 109 items/year from the river to the sea across both seasons. Additionally, hydrological regimes, tidal forces, and human activities were identified to influence MPs abundance and flux. This quantitative analysis establishes a mechanistic framework for understanding hydrological impacts on estuarine MPs transport, providing critical baseline data for developing targeted pollution management strategies in coastal ecosystems.

Robust mussel-inspired LBL carbon nanotube-based superhydrophobic polyurethane sponge for efficient oil–water separation utilizing photothermal effect - Guoyan Yang; Yuxin Zhang; Zuozhu Yin; Yuanting Deng; Zihao Li; Yu Xie; Yuhua Chen; Chenggang Yang; Haitao Yang; Yidan Luo; Zhen Hong; Mingshan Xue (Fuel, 2025)

Differentiation and characterization of non-thymomatous ocular myasthenia gravis children with CT - Youran Cai; Zhongyuan Cheng; Yuanting Yang; Baojun Xu; Qiwen Feng; Xu Liu; Jian Chen; Qing Zhou (Acta Neurologica Belgica, 2025)

Characteristics of Higher Harmonic Forces on Submerged Horizontal Cylinders with Sharp and Round Corners - Hongfei Mao; Jinwen Zeng; Guanglin Wu; Hanqing Chen; Shuqin Zhang; Yuanting Yang; Qinru Yang (Journal of Marine Science and Engineering, 2024)
In this study, a two-phase flow numerical wave tank model based on the viscous flow theory was applied to conduct computational research on the interaction between waves and submerged horizontal cylinders. The research objective is to reveal the hydrodynamic characteristics of nonlinear loads on submerged horizontal cylinders with a focus on vortex effects. The influence of the sharp and round corners of cross-sections on the wave forces on cylinders was summarized. The reasons for the characteristics of the wave forces were explained by analyzing the flow field distribution around the cylinder and decomposing the wave forces into inertial and drag forces. This study found that under the various incident wave amplitudes, the section corner and aspect ratio have significant impacts on each frequency component of the horizontal and vertical wave forces. The distribution of the vorticity field shows that the vortex effects lead to the differences between the loads on the cylinder under different cross-sectional corners and aspect ratios. The characteristics of inertial forces and drag forces on the cylinders were given by comparing and analyzing the cases with different sectional sharp and round corners. The inertia and drag coefficients were obtained by solving Morison’s equation. Under various Kc and Re numbers, the maximum values of the inertia and drag coefficients obtained are significantly different from those for submerged cylinders under oscillatory flow action.

Deciphering the stability mechanism of Pt-Ni/Al2O3 catalysts in syngas production via DRM - Rui Zhao; Kun Cao; Rongli Ye; Yuanting Tang; Chun Du; Fudong Liu; Yunkun Zhao; Rong Chen; Bin Shan (Chemical Engineering Journal, 2024)

Facile construction of multifunctional 3D smart MOF-based polyurethane sponges with photocatalytic ability for efficient separation of oil-in-water emulsions and co-existing organic pollutant - Qidong Zha; Yuankun Yao; Zuozhu Yin; Yuanting Deng; Zihao Li; Yu Xie; Yuhua Chen; Chenggang Yang; Yidan Luo; Mingshan Xue (Chemical Engineering Journal, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

Roles of extracellular vesicles on macrophages in inflammatory bone diseases - Yifan Lin; Ziyan Wang; Shirong Liu; Jiaohong Liu; Zhiyi Zhang; Yuanting Ouyang; Zhikang Su; Ding Chen; Lvhua Guo; Tao Luo (Molecular and Cellular Biochemistry, 2024)

Asymmetric phosphorylation integrating host feature and blue thermally activated delayed fluorescence of thiaxanthene S,S-dioxide emitter for efficient heavily doped white organic light-emitting diodes - Yingying Chen; Chao Wang; Peng Ma; Yuanting Guo; Yuetong Liu; Aiqi Dang; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Thin and soft Ti3C2Tx MXene sponge structure for highly sensitive pressure sensor assisted by deep learning - Wang Guo; Zhiqiang Ma; Zhou Chen; Haojun Hua; Dong Wang; Mohamed Elhousseini Hilal; Yatian Fu; Pengyi Lu; Jian Lu; Yuanting Zhang; Derek Ho; Bee Luan Khoo (Chemical Engineering Journal, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

Impacts of physical activity and particulate air pollution on the onset, progression and mortality for the comorbidity of type 2 diabetes and mood disorders - Huihuan Luo; Yuxin Huang; Qingli Zhang; Kexin Yu; Yuanting Xie; Xia Meng; Haidong Kan; Renjie Chen (Science of The Total Environment, 2023)

Cholinergic anti-inflammatory pathway mediates diesel exhaust PM2.5-induced pulmonary and systemic inflammation - Yuanting Xie; Shimin Tao; Bin Pan; Wenhui Yang; Wenpu Shao; Xinyi Fang; Dongyang Han; Jingyu Li; Yubin Zhang; Renjie Chen; Weihua Li; Yanyi Xu; et al. (Journal of Hazardous Materials, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

A harsh environment resistant robust Co(OH)2@stearic acid nanocellulose-based membrane for oil-water separation and wastewater purification - Zuozhu Yin; Min Li; Zihao Li; Yuanting Deng; Mingshan Xue; Yuhua Chen; Junfei Ou; Sheng Lei; Yidan Luo; Chan Xie (Journal of Environmental Management, 2023)

Testosterone attenuates senile cavernous fibrosis by regulating TGFβR1 and galectin-1 signaling pathways through miR-22-3p - Zongren Hu; Yuanting Zhang; Jisong Chen; Min Luo; Neng Wang; Yinfu Xiao; Qinghu He (Molecular and Cellular Biochemistry, 2023)

Adaption of tobacco rattle virus to its solanaceous hosts is related to the codon usage bias of the hosts and that of the viral 16 K gene - Qi Lin; Yuanting Zheng; Yueyan Yin; Yi Chen; Miaomiao Li; Hongying Zheng; Jianping Chen; Fei Yan; Yuwen Lu; Shengchun Xu (European Journal of Plant Pathology, 2023)

Highly active and durable nitrogen-doped CoP/CeO2 nanowire heterostructures for overall water splitting - Lili Zhang; Yuanting Lei; Wenjing Xu; Dan Wang; Yafei Zhao; Wenxing Chen; Xu Xiang; Xinchang Pang; Bing Zhang; Huishan Shang (Chemical Engineering Journal, 2023)

The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs - Yixing Pi; Zitian Liang; Qianzhou Jiang; Ding Chen; Zhikang Su; Yuanting Ouyang; Zhiyi Zhang; Jiaohong Liu; Siyi Wen; Li Yang; Tao Luo; Lvhua Guo (Chemico-Biological Interactions, 2023)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

The monthly variation tendency of microcystin-LR levels in the Huangpu River (China) by applications of ELISA and HPLC - Sijia Hua; Jiawen Chen; Liang Wu; Xinyue Yu; Jing Ye; Yuanting Li; Yongqiang Zhu; Fuxiang Tian (Environmental Science and Pollution Research, 2022)

Wave-dominated, mesotidal headland-bay beach morphodynamic classsfications of the Shuidong Bay in South China - Jitao Yu; Yuanting Ding; Huangxin Cheng; Lailiang Cai; Zishen Chen (Acta Oceanologica Sinica, 2016)